Jump height loss as an indicator of fatigue during sprint training - Jiménez-Reyes, P.; Pareja-Blanco, F.; Cuadrado-Penafiel, V.; Ortega-Becerra, M.; Párraga, J.; González-Badillo, J. J. (Journal of Sports Sciences, 2019)
This study analysed the acute mechanical and metabolic responses to a sprint training session focused on maintaining maximal speed until a given speed loss was reached. Nine male high-level sprinters performed 60 m running sprints up to a 3% in speed loss with 6 min rests between sets. Mechanical responses (countermovement jump (CMJ) height and speed loss) and metabolic responses (blood lactate and ammonia concentrations) were measured pre-exercise and after each set was performed. Jump height loss showed almost perfect relationships with both lactate (r = 0.91) and ammonia (r = 0.91) concentrations. In addition, nearly perfect relationships were observed for each athlete between CMJ height loss and lactate (r = 0.93-0.99) and ammonia (r = 0.94-0.99). Very large correlations were found between speed loss and lactate (r = 0.83), and ammonia (r = 0.86) concentrations. Furthermore, close relationships were observed for each athlete between speed loss and lactate (r = 0.86-0.99), and ammonia (r = 0.88-0.98). These results suggest that the CMJ test may allow more accurate setting of training loads in sprint training sessions, by using an individualised sprint dose based on mechanical and physiological responses rather than a standard fixed number of sprints for all athletes.